Modul Bimbingan dan Konseling Untuk Mencegah Stres Siswa Pada Masa Pandemi Covid-19 - M Fauzi Hasibuan; Jamila Jamila; Dina Puspita; Hendra Sucitra; Fajrina Ulfa (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
This research aims to formulate the feasibility of guidance and counseling modules to prevent student stress in the covid-19 pandemic as well as ability by BK teachers/counselors in junior high school. This research method uses the ADDIE model. The study test subjects consisted of three experts to test eligibility, and three BK teachers/counselors. Instruments used are sklala likert, questionnaire and Focus Group Discussion (FGD). The data of the results of the study was analyzed using descriptive analysis and nonparametric statistical analysis. The findings show that this guidance and counseling module can be utilized by BK teachers/counselors to assist teachers in preventing student stress during the covid-19 pandemic